Identification of the Replication Origins from Cyanothece ATCC 51142 and Their Interactions with the DnaA Protein: From In Silico to In Vitro Studies - Huang, He; Song, Cheng-Cheng; Yang, Zhi-Liang; Dong, Yan; Hu, Yao-Zhong; Gao, Feng (Frontiers in Microbiology, 2015)
Based on the complete genome of Cyanothece ATCC 51142, the oriCs of both the circular and linear chromosomes in Cyanothece ATCC 51142 have been predicted by utilizing a web-based system Ori-Finder. Here, we provide the experimental supports for the results of Ori-Finder to identify the origins of replication of Cyanothece ATCC 51142 and their interactions with initiator protein DnaA . The two replication origins are both composed of three characteristically arranged DnaA boxes, and an AT-rich stretch, and the oriC in circular chromosome is followed by the dnaN gene. The dnaA gene is located downstream of the origin of circular chromosome and expresses a typical DnaA protein that follows the division into four domains (I, II, III, IV), as with other members of the DnaA protein family. Here, we report the purification of DnaA (IV) and characterize the interaction of the purified protein with the replication origins, in order to offer experimental supports for the prediction. Combined with experimental validation, we identified the oriCs of Cyanothece ATCC 51142. The results of EMSA and DNase I footprint assay demonstrate that the C-terminal domain of Cyanothece ATCC 51142 DnaA protein specifically binds the oriCs of both the circular and linear chromosomes, and DNase I footprint assay demonstrates that DnaA (IV) has a hypersensitive affinity interaction with DnaA boxes in both oriCs. The results also confirm the results predicted by Ori-Finder.